Tratamento de efluente de matadouro e frigorífico de suínos utilizando a eletrocoagulação: avaliação dos parâmetros operacionais - Paloschi, Vanessa Nayara (2020)
The effluent from swine slaughterhouses, is rich in organic matter and microbial load, requiring adequate treatment to be ableto be dumped into a water body. Thus, the objective of this work was to evaluate the best conditions for the treatment of wastewater fromswine slaughterhouse,through the application of the electrocoagulation process, determine the energy cost and evaluate the sludge generated by the process. The study was carried out in two stages, where a complete factorial design 23was prepared for each of the stages. In this approach, an electrocoagulation system with a capacity of 1 L was elaboratefor batch operation, using aluminum electrodes and a stirring paddle, aiming at removing Color, Turbidity and Chemical Oxygen Demand (COD). Initially, in the planning of the first stage, operating parameters were evaluated in terms of the efficiency of removing the response parameters, where the distance of electrodes was fixed at 5 cm, initial pH of 6.76, temperature of 23ºC and electrolysis time of5 to 30 minutes, electric current applied from 0,4 to 1,0 A and rotation from 15 to 90 rpm. The results showed a good removal with efficiencies around 97% for Color and Turbidity and 80% for COD. The sludge generated in this first stage of electrocoagulation was also analyzed, quantifying the aluminum (4.1mg kg-1) present in it. Subsequently, the experiments were conducted in a second stage, based on the results of the previous stage, the values of the independent variables were adjusted to obtain the models of the response variables and consequently achieving the overall desirability of the system. This time varying the intensity of the current (0.01 to 0.7 A) and changing the rotation (15 to 100 rpm). Thus, it was possible to determine the ideal condition for treating the swine slaughterhouse effluent by electrocoagulation,where the current density was15.66mA cm-2, initial pH 6.95, distance between electrodes of 0.5 cm during 26 minutes of operation, rotation of 93 rpm and electric current of 0.47 A, that hadan average removal of 71.12%, 87.38% and 98.50% that corresponds to COD, color and turbidity, respectively In addition to these removal parameters, the removal of total Kjeldahl Nitrogen (34.17%) and Total Phosphorus (99.56%) was also quantified. This same condition presented 3996,96 KWh per cubic meter of electricity and 4,91981x10-4g m³of aluminum, at a cost of R$ 2.07 excluding taxes and R$ 3.19 with taxes. Electrocoagulation proved to be an efficient method of removing pollutants from swine slaughterhouse effluents, especially when the appropriate parameters have been applied.